2016
DOI: 10.1371/journal.pone.0159233
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of NIPT in Detection of Chromosomal Copy Number Variants Using Low-Coverage Whole-Genome Sequencing of Plasma DNA

Abstract: ObjectivesThe aim of this study was to assess the performance of noninvasively prenatal testing (NIPT) for fetal copy number variants (CNVs) in clinical samples, using a whole-genome sequencing method.MethodA total of 919 archived maternal plasma samples with karyotyping/microarray results, including 33 CNVs samples and 886 normal samples from September 1, 2011 to May 31, 2013, were enrolled in this study. The samples were randomly rearranged and blindly sequenced by low-coverage (about 7M reads) whole-genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…Noninvasive prenatal testing has been recommended as a first‐tier or second‐tier screening test for fetal common trisomies, with lower false‐positive rates and higher positive predictive values than serum biochemical screening . Noninvasive prenatal testing can also enable the detection of other aneuploidies, including sex chromosome aneuploidies (SCA) and structural chromosomal abnormalities . However, most of the published data have mainly focused on 3 common aneuploidies, SCA, and subchromosomal deletions/duplications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive prenatal testing has been recommended as a first‐tier or second‐tier screening test for fetal common trisomies, with lower false‐positive rates and higher positive predictive values than serum biochemical screening . Noninvasive prenatal testing can also enable the detection of other aneuploidies, including sex chromosome aneuploidies (SCA) and structural chromosomal abnormalities . However, most of the published data have mainly focused on 3 common aneuploidies, SCA, and subchromosomal deletions/duplications.…”
Section: Introductionmentioning
confidence: 99%
“…2 Noninvasive prenatal testing can also enable the detection of other aneuploidies, including sex chromosome aneuploidies (SCA) and structural chromosomal abnormalities. [3][4][5][6][7] However, most of the published data have mainly focused on 3 common aneuploidies, SCA, and subchromosomal deletions/duplications. Reports on the incidence and pregnancy outcome of autosomal aneuploidies other than common trisomies detected at NIPT are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Therefore, the NIPT sequencing data analysis would be affected correspondingly, especially for CNVs near the telomeres and centromeres. 8 With current techniques, NIPT cannot exhibit high performance in detecting genome-wide CNVs, but in a selected few chromosome aberrations, such as 22q11.2 microdeletion. 11 In our study, NIPT showed higher performance in detecting smaller sizes CNVs than previous studies, 7,8 demonstrating the improved technology of NIPT was independent with CNVs size.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, non‐invasive detection of foetal CNVs was encouraged by the successful application of NGS on cffDNA in screening for aneuploidy. Li et al and Liu et al illustrated that NIPT exhibited higher performance in detecting large CNVs, and the detection power for smaller CNV sizes decreased when the same sequencing depth was used to detect aneuploidy. Yin et al and Lo et al illustrated the variation in detection power among CNVs of the same size, but at different sequencing depths and foetal fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Noninvasive prenatal testing (NIPT) has evolved into an important routine clinical practice. Numerous variations on experimental and in silico procedures have been shown to reliably detect fetal chromosomal aneuploidies, mostly concerning trisomies 13, 18, and 21 . The accuracy of NIPT seems high; however, as fetal fragments are scattered throughout a more abundant maternal background in blood plasma, individual performance highly depends on the fraction of fetal‐derived cell‐free DNA (FF).…”
Section: Introductionmentioning
confidence: 99%